2017
DOI: 10.1111/geb.12594
|View full text |Cite
|
Sign up to set email alerts
|

A global geography of synchrony for marine phytoplankton

Abstract: Aim: Spatial synchrony in plankton is imperfectly understood yet may have far-reaching implications, for example for carbon export to the deep ocean. Several techniques have been used to describe patterns of spatial synchrony, from correlation coefficients to spectral methods. Some studies have used temporally extensive data sets to identify causes of synchrony. This study instead uses the exceptional spatial extent provided by remotely sensed data to describe, for the first time as far as we know, geographica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 52 publications
(90 reference statements)
2
47
0
Order By: Relevance
“…A few prior studies have used this tool. For instance, Defriez and Reuman mapped global spatial variation in synchrony of marine chlorophyll a (Defriez & Reuman in press b ) and terrestrial vegetation (Defriez & Reuman in press a ), and used spatial statistics to infer causes of synchrony from the spatial patterns obtained. This map‐based approach is discussed in more detail in the fourth section.…”
Section: Application: Inference Of the Causes Of Synchronymentioning
confidence: 99%
See 3 more Smart Citations
“…A few prior studies have used this tool. For instance, Defriez and Reuman mapped global spatial variation in synchrony of marine chlorophyll a (Defriez & Reuman in press b ) and terrestrial vegetation (Defriez & Reuman in press a ), and used spatial statistics to infer causes of synchrony from the spatial patterns obtained. This map‐based approach is discussed in more detail in the fourth section.…”
Section: Application: Inference Of the Causes Of Synchronymentioning
confidence: 99%
“…A recent approach measures synchrony in neighbourhoods defined by a moving window. For each location, some metric of average synchrony among nearby locations is computed; these values are then mapped (Defriez & Reuman in press a,b ). We apply this method to 1989–1998 time series of annual peak terrestrial vegetation greenness (NDVI) derived from Advanced Very High Resolution Radiometer (AVHRR) satellite imagery for the contiguous USA (Fig.…”
Section: Mapping Spatial Variation In Synchronymentioning
confidence: 99%
See 2 more Smart Citations
“…However, our new result that geographies of synchrony in temperature and precipitation are important correlates of the geography of EVI synchrony, while true, does not follow automatically from the earlier knowledge. Defriez & Reuman () found that the geography of synchrony of incident solar irradiance was not statistically related to the geography of synchrony in chlorophyll a abundance in the world's oceans, even though it is well known that irradiance can be an important factor in chlorophyll a dynamics. In complex ecosystems, known importance of an environmental factor for ecological dynamics does not necessarily mean that the factor produces a Moran effect or a geography of synchrony, for several potential reasons, including the following: the possibility that the environmental factor itself has a muted geography of synchrony; and the possibility that the factor's influence on vegetation is nonlinear or complex in some important way that varies geographically (see, e.g., Defriez & Reuman, , where mechanisms are discussed for the phytoplankton case).…”
Section: Discussionmentioning
confidence: 99%